2022
DOI: 10.1093/ije/dyac032
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the pandemic: mortality trends and seasonality of deaths in Australia in 2020

Abstract: Aim To assess whether the observed numbers and seasonality of deaths in Australia during 2020 differed from expected trends based on 2015–19 data. Methods We used provisional death data from the Australian Bureau of Statistics, stratified by state, age, sex and cause of death. We compared 2020 deaths with 2015-19 deaths using interrupted time series adjusted for time trend and seasonality. We measured the following outcomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…The estimated excess mortality in Korea was -29,124 (-55 per 100,000 persons). The O/E ratio was 0.91, which is lower than that in Australia (0.96) [ 26 ] or Japan (0.98) [ 27 ], despite the difficulty in undertaking a direct comparison due to methodological differences. Region had little effect on excess mortality in 2020.…”
Section: Discussionmentioning
confidence: 80%
“…The estimated excess mortality in Korea was -29,124 (-55 per 100,000 persons). The O/E ratio was 0.91, which is lower than that in Australia (0.96) [ 26 ] or Japan (0.98) [ 27 ], despite the difficulty in undertaking a direct comparison due to methodological differences. Region had little effect on excess mortality in 2020.…”
Section: Discussionmentioning
confidence: 80%
“…In Australia, wherein no major COVID-19 pandemic wave was registered in 2020, ADRD-related deaths decreased by 5% compared with the expected numbers obtained from the 2015–19 time series. 29 In the USA, the excess in age-standardized mortality rates for AD in 2020 was 8.7% more compared with 2019 with differences across ethnic groups. 30 Other studies reporting an excess in ADRD-related deaths did not include all data from 2020 and were limited to the first pandemic wave; Grande et al 7 reported a +13.9% excess (March–April) in Italy and Wu et al 8 reported an excess of +28% (March–June) in England and Wales.…”
Section: Discussionmentioning
confidence: 96%
“…In the international literature, analyses of mortality by cause of death in 2020 remain limited. However, the observations show differences between countries 31,32,33 . Unlike France, most countries report an increase in mortality for diseases of the circulatory system in 2020.…”
Section: Another French Exceptionmentioning
confidence: 90%